Analysis of gunshot damage to the porcine femur in a human thigh model using 5.5 mm airgun pellet: 3D reconstruction of gunshot injuries. - Mateusz Wilk; Małgorzata Chowaniec; Elżbieta Chowaniec; Grzegorz Bajor (PLoS ONE)
The performance of advanced air rifles available on the market is comparable to that of small-calibre firearms. The airgun market offers airgun pellets that vary in weight, shape, calibre and material. In view of the ease of airguns tuning, a study of the gunshot damage to the anterior surface of the porcine femoral shaft was carried out with shots fired from a 5.5 mm calibre air rifle. An original human thigh model using a pig femur embedded in ballistic gellatine was used in the study. Gunshot damage was inflicted by firing Haendler&Natterman Baracuda, HollowPoint, Spitzkugel and Excite Apollo 5.5 mm airgun pellets from an Air Arms s410 Hi-Power Xtra FAC 5.5 mm calibre PCP air rifle. Measurements of the velocity and impact energy of the pellets as well as the extent of the bone and periosteal entry damage were taken. Statistical analysis was used to identify differences between pellets with regard to dimensions of gunshot damage to the shafts of the femur. Selected models were subjected to CT imaging.